UJI PUPUK ORGANIK CAIR (POC) DARI BEBERAPA LEGUM DAN NPK ORGANIK TERHADAP PERTUMBUHAN SERTA HASIL TOMAT (Lycopersicum esculentum L.) - Riska Febri Amalia; Fathurrahman F (DINAMIKA PERTANIAN, 2024)
This study examines the main and interaction effects of liquid organic fertilizers derived from various legume plants, as well as the dosage of Organic NPK, on the growth and yield of tomato plants. Conducted as a 4 x 4 factorial experiment within a completely randomized design, the research included three replications and focused on two factors. The first factor examined was the Liquid Organic Fertilizer (LOF) from different legume plants, featuring four levels: no LOF application, LOF from lamtoro, LOF from rain tree, and LOF from peanuts. The second factor was the dosage of Organic NPK fertilizer, implemented at four levels: 0, 15, 30, and 45 g/plant. The observed parameters included plant height, flowering age, harvest age, the number of productive branches, fruit count per plant, total weight per plant, weight per fruit, and the number of leftover fruits. The collected data was statistically analyzed and further assessed using the HSD test at a 5% significance level. The findings revealed that the interaction between LOF from various legume plants and the organic NPK dosage significantly affected all parameters, except plant height and fruit weight. The optimal treatment combined the LOF from trembled leaves with an organic NPK dosage of 45 g/plant. Additionally, the primary effect of LOF from different legumes was significant across all observation parameters, with the most effective treatment being the LOF from trembles. The impact of organic NPK fertilizer was also evident in all measured parameters, with the best dosage being 45 g/plant.